POLISH EXPERIENCE IN THE FIELD OF RENEWABLE ENERGY SOURCES USE AS THE EXAMPLE FOR REPUBLIC OF MOLDOVA - Tirshu M. (Problems of the Regional Energetics)
In the given paper results of business trip to Poland of laboratory chief M.Tirshu are presented concerning experience of use of renewed energy sources in distinct Pomorsk, and also useful recommendations for Republic Moldova at use of experience of Poland in this field.